Graphene/MoS2/FeCoNi(OH)x and Graphene/MoS2/FeCoNiPx multilayer-stacked vertical nanosheets on carbon fibers for highly efficient overall water splitting - Xixi Ji; Yanhong Lin; Jie Zeng; Zhonghua Ren; Zijia Lin; Yongbiao Mu; Yejun Qiu; Jie Yu (Nature Communications)
Abstract Development of excellent and cheap electrocatalysts for water electrolysis is of great significance for application of hydrogen energy. Here, we show a highly efficient and stable oxygen evolution reaction (OER) catalyst with multilayer-stacked hybrid structure, in which vertical graphene nanosheets (VGSs), MoS2 nanosheets, and layered FeCoNi hydroxides (FeCoNi(OH)x) are successively grown on carbon fibers (CF/VGSs/MoS2/FeCoNi(OH)x). The catalyst exhibits excellent OER performance with a low overpotential of 225 and 241 mV to attain 500 and 1000 mA cm−2 and small Tafel slope of 29.2 mV dec−1. Theoretical calculation indicates that compositing of FeCoNi(OH)x with MoS2 could generate favorable electronic structure and decrease the OER overpotential, promoting the electrocatalytic activity. An alkaline water electrolyzer is established using CF/VGSs/MoS2/FeCoNi(OH)x anode for overall water splitting, which generates a current density of 100 mA cm−2 at 1.59 V with excellent stability over 100 h. Our highly efficient catalysts have great prospect for water electrolysis.